INFLAMMATORY AND IMMUNOLOGICAL ASPECTS OF TISSUE REACTION BY POLYPROPYLENE IMPLANTS IN EXPERIMENT WITH ANIMALS - Игорь Александрович Эйзенах; Максим Александрович Бакарев; Галина Анатольевна Лапий; Вадим Гельевич Мозес; Кира Борисовна Мозес (Медицина в Кузбассе, 2020)
The aim of research – to study and compare the cells’ structure of infiltration around polypropylene material in different time and to compare the results of immunohistochemical parameters in around implant and intact tissue of experimental animals in 12 months after implantation.